The Pengaruh Paritas dan Akses Informasi Kesehatan Terhadap Pengetahuan Ibu Hamil Mengenai Kegawatdaruratan Dalam Kehamilan di Puskesmas Panekan, Kabupaten Magetan: Pregnancy - iik bekti budyawati; Triana Septianti Purwanto; subagyo subagyo (Jurusan Kebidanan Politeknik Kesehatan Kemenkes Surabaya, 2021)
Pregnancy can be a determinant of maternal and fetal well-being. Lack of maternal knowledge in emergencies during pregnancy is one of the causes of a lack of early detection which causes a lack of anticipation of the dangers of pregnancy. To prove the effect of parity and access to the health information on the knowledge of pregnant women regarding emergency pregnancies at Panekan Health Center. This study is an analytical study that is cross-sectional. Samples were taken with a sampling technique of 80 respondents. Data collection using a closed questionnaire. The influence of the dependent and independent variables was tested using Linear Regression with p-value <0.005. The results of the statistical test using linear regression on the variable parity to the knowledge of pregnant women obtained a value of p = 0.022 so that there is an influence between parity and knowledge of pregnant women regarding the emergency of pregnancy. The results of statistical tests on health information access variables on the knowledge of pregnant women using linear regression obtained p-value = 0,000 so that there is a significant influence between access to health information with the knowledge of pregnant women regarding emergency pregnancies. This is also supported by the results of the significance tests of the three variables tested together using linear regression which shows 0,000. The concluded that there is an influence of parity and access to health information on the knowledge of pregnant women regarding emergency pregnancies at Panekan Health Center, Magetan Regency.